How Structural Deficiencies Hamper Estonia’s Catching-up Process. Strukturschwächen als Hemmnis für Estlands Aufholprozess - Schrader, Klaus; Laaser, Claus-Friedrich; Benček, David (Estonian Discussions on Economic Policy, 2016)
Estonia is widely regarded as a paramount example for a successful transformation of a socialist economic system to a functioning market economy. Against the backdrop of this positive image which contrasts strongly with the crisis scenarios in Southern Europe the remaining problems of Estonia are often ignored. Estonia has hardly succeeded in catching-up economically with the richer countries of the EU. In this paper the authors raise the question why the catching-up process of Estonia is not as successful as it could have been expected from the policy performance during the last decades. It turns out that Estonia faces a serious productivity problem, particularly in the manufacturing sector producing tradable goods which is normally the driving engine behind economic and technological catching-up. The Estonian economy has failed to undergo the necessary structural change towards technologically more advanced employment structures and export patterns. Accordingly, Estonian economic policy needs to create a suitable business environment to support this kind of structural change.